STRATEGI EQUILIBRIUM PASAR TRADISIONAL MENSIASATI KEPUNGAN PASAR MODERN - Widodo, Tri; Wardani, Bertha Kusuma (AMONG MAKARTI, 2012)
The market is a rotation of the economy of a region / country, which is perfect because many parties are involved in it. However, nowadays traditional markets face great challenges with the advent of modern markets, which give it a more modern markets such as the quality and type of product, convenience, cleanliness, other facilities that support it. Traditional markets mengimbangai find it difficult to compete with the more modern marketplace. The survey results demonstrate that the rate of growth in traditional markets fell by 8,1%, while the modern market to increase growth rates 31,4%. It if allowed to continue will bring economic imbalances. Thus, the purpose of this study was to determine the limiting factors of traditional markets and provide solutions that balance the traditional market to compete with modern market economy so that the wheels can be balanced. This research is qualitative research. The sample in this study are the traditional and modern markets Salatiga. The data in this study is primary data obtained by observation and direct interviews with market participants and consumers Salatiga. The results of this study indicate that the mindset of traditional market participants are still difficult to change to make a change for the better in competition with the modern market. In addition, the design and appearance of market factors, spatial layout, variety and quality of goods, sales promotion, market operating hours are limited, and optimizing the utilization of the selling space is also the biggest weakness of traditional markets in the face of competition with the modern market. Therefore, to balance the creation of market participants should take an active role to create an atmosphere and better market conditions, clean, comfortable, and safe. In addition it is also necessary, government intervention in the regulation / legislation relating to the design and layout of the market between the traditional and modern, as well as infrastructure support facilities. Keywords: Traditional Market, Modern Market, Strategy Equilibrium